Modelling of Twin Rotor MIMO system - Dang Huu, T. (Institute of Electrical and Electronics Engineers Inc., 2017)
This paper presents an approach to model Twin Rotor MIMO System (TRMS). For simplicity, the model is separated into three channels: vertical, horizontal, and cross-coupling channels. A hybrid method, a cooperation between first principle method and optimal algorithm, is used to analyse and model the system. Unknown parameters of the model are estimated by physical experiments and Genetic Algorithm. The pith and yaw outputs of the identified model in simulation and the real system with the same several types of inputs are compared with each other. © 2016 IEEE.